2012
DOI: 10.1002/hep.25691
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of microRNA 506 leads to decreased Cl−/HCO3− anion exchanger 2 expression in biliary epithelium of patients with primary biliary cirrhosis

Abstract: Cl−/HCO3−anion exchanger 2 (AE2) participates in intracellular pH homeostasis and secretin-stimulated biliary bicarbonate secretion. AE2/SLC4A2 gene expression is reduced in liver and blood mononuclear cells from patients with primary biliary cirrhosis (PBC). Our previous findings of hepatic and immunological features mimicking PBC in Ae2-deficient mice strongly suggest that decreased AE2 expression might be involved in the pathogenesis of PBC. Here we tested the potential role of hsa-microRNA 506 (miR-506) – … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
178
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 206 publications
(180 citation statements)
references
References 45 publications
2
178
0
Order By: Relevance
“…Interestingly, cholangiocytes in PBC patients show suppressed anion exchanger (AE2; SLC4A2), which is possibly caused by upregulated micoRNA-506, which result in impaired biliary HCO 3 -formation [44] . This may cause impaired 'biliary HCO 3 -umbrella,' which protects cholangiocytes against the toxic effects of human hydrophobic bile acids [44] . GCDC is a major hydrophobic bile acid in cholestasis and impaired umbrella may result in GCDC-induced cholangiocyte damage [3,4] .…”
Section: Udca and Tauro-udca As A Suppressor Of Er Stress And Deregulmentioning
confidence: 99%
“…Interestingly, cholangiocytes in PBC patients show suppressed anion exchanger (AE2; SLC4A2), which is possibly caused by upregulated micoRNA-506, which result in impaired biliary HCO 3 -formation [44] . This may cause impaired 'biliary HCO 3 -umbrella,' which protects cholangiocytes against the toxic effects of human hydrophobic bile acids [44] . GCDC is a major hydrophobic bile acid in cholestasis and impaired umbrella may result in GCDC-induced cholangiocyte damage [3,4] .…”
Section: Udca and Tauro-udca As A Suppressor Of Er Stress And Deregulmentioning
confidence: 99%
“…One interesting finding has been reported by Banales et al, who observed upregulation of miR-506 in primary biliary cirrhosis. The authors show that miR-506 regulates expression of the Cl − /HCO3 − anion exchanger 2 (AE2) and that suppression of miR-506 leads to improved AE2 function in primary biliary cirrhosis cholangiocytes [85]. In addition, Glaser et al reported that, after hepatic injury, secretin produced by cholangiocytes and S cells reduced miR125b and let7a levels, resulting in up-regulation of VEGF and NGF.…”
Section: Biliary Treementioning
confidence: 97%
“…PBC patients have significantly decreased levels of AE2. Banales et al demonstrated that miR-506, upregulated in cholangiocytes from PBC patients, could bind the 3′ UTR of AE2 mRNA and prevent protein translation, leading to diminished AE2 activity and impaired biliary secretory functions [174]. Recently, Ananthanarayanan et al reported that miR-506 was also responsible for a decreased level of InsP 3 R3 [173], an intracellular Ca channel that is concentrated along the subapical portion of the endoplasmic reticulum where it regulates bicarbonate HCO 3 − and Cl− to support the functions of AE2.…”
Section: Micrornamentioning
confidence: 98%